Radioactive Iodine-129 Capture in Mixed Cation Sodalites: ab initio Modelling. (4th March 2018) - Kuo, E.Y.; Gregg, D.J.; Vance, E.R.; Maddrell, E.R.; Lumpkin, G.R.
Abstract: Sodalites have been investigated experimentally for the capture and long-term containment of 129 I, a significant and hazardous waste product of the nuclear fuel cycle. Sodalites are zeolite-type structures commonly occurring in nature in alkaline igneous rocks and having the prototype formula Na8 (AlSiO4 )6 Cl2 . The crystal structure is based around β-cages consisting of corner-sharing SiO4 and AlO4 tetrahedra. In the centre of the β-cage is an anion X. Iodine captured by sodalites sits in the centre of the β-cages as iodide anions. Silver iodide (AgI) plays an important role in the capture and subsequent processing of 129 I in the nuclear fuel cycle. Using ab initio density functional theory (DFT) modelling, we investigate the energetics and feasibility of iodine capture and containment in mixed cation sodalites Na8-x Agx (AlSiO4 )6 I2, and compare the results with experimental observations.